An analysis of litigation strategies for the attainment of water justice in South Africa - Mapitsa, Cosmo Pahlahle (Department of Public Law, 2019)
Jurisprudence on water justice is fractured, and this dissertation explores a range of causal factors for the way it has developed. Firstly, water justice is defined as a concept, and it is argued that the concept remains weakly theorised, with discussion on the reasons some components are better reflected in law than others. Then, the process of litigation as a means of obtaining water justice is explained within the context of other strategies for seeking justice. Finally, the development of jurisprudence is analysed using the components of water justice outlined in the study. The research found that some components of water justice are more prominent in jurisprudence than others. Interviews with litigators explained a range of causal reasons for this, including a need for communities to have access to water in a timely manner, and a need by courts to have cases that are clear; based on sound and available evidence. Building jurisprudence requires incremental change, and litigators face a variety of priorities informing their strategies. Furthermore, while litigation plays an important role in attaining water justice, it is most effective in combination with other approaches. This study asserts that there is significant scope for a diversity of interested parties to collaborate and build integrated approaches to attaining water justice.